A aplicação da teoria das restrições em uma empresa do ramo de moda: um estudo de caso - Rebouças, Lyandra Amel Beserra (2024)
The fashion sector in Brazil is one of the most important and profitable in the country, with an annual revenue of over R$150 billion. However, the sector faces considerable challenges, especially in 2024, due to economic factors that affect the competitiveness of national companies. In this scenario, the Theory of Constraints (TOC) is presented as a promising approach to address bottlenecks in the production process. Developed by Eliyahu M. Goldratt, TOC proposes that the performance of any system is limited by a small number of constraints, and the identification and effective management of these constraints can lead to significant improvements in productivity and efficiency. Therefore, this work aims to apply the Theory of Constraints (TOC) and generate improvements in the collection development sector of a fashion company. To this end, the methodology of the work followed by mapping the "as is" and "to be" processes, applying the five TOC focusing steps, and analyzing the results obtained. As a result, the study observed a significant improvement in the performance of the process identified as a bottleneck, with a reduction in process delays and an improvement in delivery performance. Specifically, the work details how the application of TOC in the collection development phase allowed the acceleration of the workflow, resulting in an 84.51% decrease in delivery delays and a 596% increase in the percentage of references delivered on time, demonstrating the effectiveness of the methodology. In summary, the study concludes that TOC is a powerful tool for optimizing processes and increasing competitiveness in the fashion market, suggesting its continuous and adaptive implementation in other sectors of the company